Metastasis suppressor NM23 limits oxidative stress in mammals by preventing activation of stress‐activated protein kinases/JNKs through its nucleoside diphosphate kinase activity. Issue 4 (11th January 2017) - Peuchant, Evelyne; Bats, Marie‐Lise; Moranvillier, Isabelle; Lepoivre, Michel; Guitton, Jérôme; Wendum, Dominique; Lacombe, Marie‐Lise; Moreau‐Gaudry, François; Boissan, Mathieu; Dabernat, Sandrine
Abstract : NME1 (nonmetastatic expressed 1) gene, which encodes nucleoside diphosphate kinase (NDPK) A [also known as nonmetastatic clone 23 (NM23)‐H1 in humans and NM23‐M1 in mice], is a suppressor of metastasis, but several lines of evidence—mostly from plants—also implicate it in the regulation of the oxidative stress response. Here, our aim was to investigate the physiologic relevance of NDPK A with respect to the oxidative stress response in mammals and to study its molecular basis. NME1 ‐knockout mice died sooner, suffered greater hepatocyte injury, and had lower superoxide dismutase activity than did wild‐type (WT) mice in response to paraquat‐induced acute oxidative stress. Deletion of NME1 reduced total NDPK activity and exacerbated activation of the stress‐related MAPK, JNK, in the liver in response to paraquat. In a mouse transformed hepatocyte cell line and in primary cultures of normal human keratinocytes, MAPK activation in response to H2 O2 and UVB, respectively, was dampened by expression of NM23‐M1/NM23‐H1, dependent on its NDPK catalytic activity. Furthermore, excess or depletion of NM23‐M1/NM23‐H1 NDPK activity did not affect the intracellular bulk concentration of nucleoside di‐ and triphosphates. NME1 ‐deficient mouse embryo fibroblasts grew poorly in culture, were more sensitive to stress than WT fibroblasts, and did not immortalize, which suggested that they senesce earlier than do WT fibroblasts. Collectively, these results indicate that the NDPK activity of NM23‐M1/NM23‐H1 protects cells from acute oxidative stress by inhibiting activation of JNK in mammal models. —Peuchant, E., Bats, M.‐L., Moranvillier, I., Lepoivre, M., Guitton, J., Wendum, D., Lacombe, M.‐L., Moreau‐Gaudry, F., Boissan, M., Dabernat, S. Metastasis suppressor NM23 limits oxidative stress in mammals by preventing activation of stress‐activated protein kinases/JNKs through its nucleoside diphosphate kinase activity. FASEB J . 31, 1531–1546 (2017) www.fasebj.org